ANALISIS MANAJEMEN STRATEGIK BISNIS TERHADAP UMKM GRAND PET SHOP - Sutjiali, Florensia; Jocelyn, Nathania; Styvani, Sherlyca; Vonnylia; Wihue Tarekar, Windy (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
This study discusses the industry analysis of Grand Pet Shop, a pet shop located in Batam City, Indonesia. The analysis focuses on the Five Forces Competition Model, Customer Value, and Industry Analysis of Grand Pet Shop as a small and medium-sized enterprise (UMKM). The results of the analysis indicate that Grand Pet Shop falls into the moderate-level strategic category. However, it is also classified as an unattractive business due to the high levels of competition, the threat of new entrants, and the threat of substitute products. Grand Pet Shop has effectively implemented customer value in its business operations. To further improve customer satisfaction and attract more clients, the author suggests that Grand Pet Shop should collaborate with veterinarians to provide services for sick or vaccinated pets. Additionally, offering discounts, rewards, and other incentives could be a viable strategy to increase the number of customers. Overall, despite the challenges in the industry, Grand Pet Shop has the potential to thrive with the right strategic adjustments and a focus on enhancing customer value.